Development of broadly protective influenza B vaccines - Gu, Chunyang; Babujee, Lavanya; Pattinson, David; Chiba, Shiho; Jester, Peter; Maemura, Tadashi; Neumann, Gabriele; Kawaoka, Yoshihiro (npj vaccines, 2025)
Influenza B viruses pose a significant threat to global public health, leading to severe respiratory infections in humans and, in some cases, death. During the last 50 years, influenza B viruses of two antigenically distinct lineages (termed ‘Victoria’ and ‘Yamagata’) have circulated in humans, necessitating two different influenza B vaccine strains. In this study, we devised a novel vaccine strategy involving reciprocal amino acid substitutions at sites where Victoria- and Yamagata-lineage viruses differ, leading to the generation of ‘hybrid’ vaccine viruses with the potential to protect against both lineages. Based on antigenic characterization, we selected two candidates and assessed their protective efficacy in a ferret model. Notably, both recombinant HA proteins conferred enhanced protection against heterologous challenges compared to their respective wild-type antigens. These findings show the potential of our novel strategy to develop cross-lineage protective influenza B virus vaccines.